2003
DOI: 10.1007/s00248-002-1062-8
|View full text |Cite
|
Sign up to set email alerts
|

Detritus Processing and Microbial Dynamics of an Aquatic Macrophyte and Terrestrial Leaf in a Thermally Constant, Spring-Fed Stream

Abstract: Past studies of organic matter processing in stream ecosystems have focused on the fate of allochthonous terrestrial leaf detritus. In streams with a reduced canopy, submerged macrophytes may provide a significant source of organic matter to the microbial community and higher trophic levels. We compared mass loss patterns and microbial dynamics between a submerged macrophyte, Sagittaria platyphylla, and a deciduous leaf, Populus deltoides. Mass loss rates were higher for the submerged macrophyte, though expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
9
1
2
Order By: Relevance
“…For example, West et al (2012) found that adding algal carbon significantly enhanced CH 4 production relative to terrestrial carbon. Although aquatic macrophyte carbon may be of lower quality than that of algae, aquatic macrophytes are generally more labile than terrestrial plants (Schlickeisen et al, 2003). For example, Tiegs et al (2013) found that terrestrial plants decomposed more slowly than aquatic macrophytes in CRD wetlands.…”
Section: Increased Organic Matter Simulationmentioning
confidence: 99%
“…For example, West et al (2012) found that adding algal carbon significantly enhanced CH 4 production relative to terrestrial carbon. Although aquatic macrophyte carbon may be of lower quality than that of algae, aquatic macrophytes are generally more labile than terrestrial plants (Schlickeisen et al, 2003). For example, Tiegs et al (2013) found that terrestrial plants decomposed more slowly than aquatic macrophytes in CRD wetlands.…”
Section: Increased Organic Matter Simulationmentioning
confidence: 99%
“…The typical substrata of aquatic hyphomycetes, i.e., litter from trees and ligneous terrestrial vegetation, however, are progressively less abundant as rivers become larger (Vannote et al, 1980). In such environments, primary production (algae, aquatic and semi-aquatic plants) is mostly autochthonous, and aquatic hyphomycetes are not good colonizers of macrophytes, even though rare studies have reported their occurrence on macrophyte detritus (Kirby et al, 1990;Schlickeisen et al, 2003). Riparian forests may, however, provide substantial amounts of leaf litter and wood even in estuarine habitats.…”
Section: Lentic and Estuarine Habitats E Stressed Freshwatersmentioning
confidence: 99%
“…Organic matter in the rhizosphere comes mainly from dead leaves, root exudates (25,38), and photosynthetic periphyton. These carbon sources plus anatomical and physiological variations relevant to periphyton growth may explain the observed differences in MeHg production between macrophytes (29).…”
mentioning
confidence: 99%